Probiotic-derived ferrichrome inhibits colon cancer progression via JNK-mediated apoptosis - Hiroaki Konishi (Nature Portfolio, 2016)
Probiotics have tumour-suppressive effects in cancer cell lines and in animal models. In this study, the authors demonstrate that ferrichrome produced by Lactobacillus caseiATCC334 can suppress colon cancer growth inducing apoptosis via the JNK pathway.